The Effects of Photobiomodulation Therapy on Post-Surgical Pain - Ezzati, Kamran; Fekrazad, Reza; Raoofi, Zeinab (Journal of Lasers in Medical Sciences, 2019)
Introduction: One of the major complains after surgery is pain. Recent advances in the prevention and reduction of postoperative pain have provided several modalities. One of them is the use of laser irradiation on the surgical area. Objectives: To evaluate the effects of low level laser therapy (LLLT) on pain and side effects after surgery. Methods: In this research, databases such as: PubMed, Science Direct, Google Scholar, Springer and Cochrane were used and the words of laser therapy, photobiomodulation, therapeutic laser, low level laser therapy, surgery and pain were searched. Articles, including systematic reviews, original articles, case series, and clinical intervention studies related to these words, were studied. The language of all articles was English and consists of papers from 2009 until 2017. Results: A total of 370 papers were studied and 10 articles that met inclusion criteria were selected for this review. Few of these articles were followed up. Surgery included a wide range of surgeries including mastectomy, breast augment post-fracture, episiotomy, tonsillectomy and hernia. The methodological quality score on the PEDro scale was between 5 and 11. 8 trials reported positive effects and 2 trials reported negative effects. In order to study clinical effect size of laser therapy after surgery, only 4 papers met entry criteria and the mean effect sizes were 0.13 to 2.77. Accordingly, the best treatment protocol included a red laser dose of 4 J/cm2 for the post-operative pain of tonsillectomy, which was irradiated through the infra mandibular angle on the tonsils. Conclusion: LLLT may be an appropriate modality for reducing pain after surgery, nevertheless the effect size of this modality is variable. Therefore, further research based on proper protocols for these patients and follow-up of therapeutic course should be designed and implemented.